Kawasaki Disease and CNS Involvement - J Gordon Millichap (Pediatric Neurology Briefs)
A 4-year-old female hospitalized with encephalopathy developed classic signs of Kawasaki disease (KD) on the fifth day after admission, in a report from the Hopital Farhat-Hached, Sousse, Tunisia, and Saint-Luc University Hospital, Brussels, Belgium.